PENGARUH PRODUK YANG BERWAWASAN HIJAU TERHADAP MINAT BELI PRODUK AIR MINUM DALAM KEMASAN MEREK ADES - Ristanti, Devi Eprilia (Manajemen Bisnis, 2015)
The research purpose?s is to analyze the effect of green-minded products on purchase intention. This research is survey. The research used a questionnaire for collecting data. The result indicated that green-minded product positively influencing purchase intention.